Central Banking Without Central Bank Money - Ize, Alain (IMF Working Papers; Working Paper ;, 1999)
Given the rapidly declining demand for central bank reserves and their gradual replacement in wholesale payments by alternative forms of money-clearinghouse moneyand treasury money-this paper discusses whether the complete extinction of base money could undermine monetary control. It argues that such concerns are misplaced since central banks can target interest rates and inflation even in the absence of base money. The paper explores implications for current and future central banking, including monetary and foreign exchange operations, lender of last resort, coordination between public debt and monetary management, and design of operating rules in currency boards.